2016
DOI: 10.1017/dmp.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Patterns in Utilization of Mental Health Services During and After Hurricane Sandy: Emergency Department and Inpatient Hospitalizations in New York City

Abstract: ObjectiveHurricane Sandy made landfall on October 29, 2012, causing a coastal storm surge and extensive flooding, which led to the closure of several health care facilities in New York City (NYC) and prolonged interruptions in service delivery. The impact on mental health–related emergency department (ED) and inpatient hospital service utilization was studied.MethodsData came from the New York Statewide Planning and Research Cooperative System. We obtained mental health–related data among NYC residents from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Our results do confirm reports from previous literature on the age effects associated with collective traumatic events, and, in terms of our findings on cohort effects, they add to the research on possible long-term mental health ramifications of exposure. The age effects associated with puberty and adolescence have been noted in previous studies that found increased risk of various mental health concerns past childhood (He et al, 2016). We interpret the period effects noted in our study as possibly indicative of a gradual effect of 9/11 and the Great Recession on mental health hospitalizations for children and adolescents.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our results do confirm reports from previous literature on the age effects associated with collective traumatic events, and, in terms of our findings on cohort effects, they add to the research on possible long-term mental health ramifications of exposure. The age effects associated with puberty and adolescence have been noted in previous studies that found increased risk of various mental health concerns past childhood (He et al, 2016). We interpret the period effects noted in our study as possibly indicative of a gradual effect of 9/11 and the Great Recession on mental health hospitalizations for children and adolescents.…”
Section: Discussionsupporting
confidence: 77%
“…No notable period effect seemed to be associated with Hurricane Sandy in 2012. A previous study examining monthly mental health hospitalizations in New York City found a considerable decrease in the count of mental health hospitalizations among all age groups restricted to the first 3 months after Hurricane Sandy and no subsequent differences from 3 through 12 months after the hurricane (He et al., ). However, the lack of period effects associated with Hurricane Sandy in our results may be due to the limited time period (1999–2013) used in the analysis.…”
Section: Discussionmentioning
confidence: 93%
“…3 Psychiatric ED visits remained higher than baseline in the six months after Hurricane Sandy in 2012. 4 ED use varied at individual hospitals after Hurricane Sandy, with visits the day of the disaster consistently lower than normal across all studies, [5][6][7] while 30% of dialysis centers experienced some degree of weather-related impact on operations in the aftermath of the June 2012 mid-Atlantic storms in the U.S. 8 An increase in all-cause admissions was found in the 30 days after Hurricane Katrina among dialysis patients. 9 Yet, evaluating hospitalizations for any cause on a 'whole disaster' scale have remained limited in the disaster health literature.…”
Section: Introductionmentioning
confidence: 93%
“…Metrics of disaster effects on health care include emergency room visits (He et al, 2016;Kandace et al, 2016), physician or clinic visits (Martin, 2015;Pantea and Lin, 2015), pharmacy use (Sharp et al, 2016), changing incidences of diseases and mortality (Greene et al, 2012;Swerdel et al, 2014), hospital discharge data bases (Rajan et al, 2015), and patient surveys on access to care (this study), among others. Addressing the physical and mental health needs of vulnerable populations (e.g.…”
Section: Introductionmentioning
confidence: 94%